Range Of Motion (ROM) Exercise dengan Frekuensi 1 Kali Per 3 Hari Dapat Meningkatkan Rentang Gerak Sendi Lutut pada Lansia dengan Gangguan Mobilitas Fisik - Muzdaliah, Ika; husaeni, hermin; Muzakkir, Muzakkir; Mutmainna, Amriati; Wijayaningsih, Kartika Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Joint flexibility decreases in the elderly due to degenerative processes in the joints, connective tissue, and cartilage. This is also caused by a reduction in the elasticity of muscle fibers, where the connective tissue in muscle fibers increases. This study aims to examine the effect of Range of Motion (ROM) exercises with a frequency of once every 3 days on improving knee joint Range of Motion in elderly individuals with physical mobility disorders. The method used is quantitative with a pre-post experimental design using a One-group pre-post test design approach. The research sample was selected using purposive sampling, with a total of 20 elderly respondents. The study was conducted in three therapy sessions on days 1, 4, and 8. The results showed a significant difference in the extension and flexion angles of the knee joint before and after the ROM therapy. The p-value obtained for both the knee extension and flexion angles was 0.000 < 0.05, indicating a significant improvement in knee joint flexibility after performing ROM exercises. In conclusion, ROM exercises performed with a frequency of once every 3 days are effective in improving knee joint Range of Motion in elderly individuals with physical mobility disorders. Therefore, this exercise is recommended as a routine intervention for the elderly at least twice a week to maintain joint flexibility and reduce the risk of mobility disorders. Keywords: Elderly, Range of Motion, Knee Joint